THE EFFECT OF DIRECT READING THINKING ACTIVITY (DRTA) ON STUDENTS’ READING COMPREHENSION : (An Experimental Study at SMA Negeri 4 Bogor) - Fajaria Lusyani (Getsempena English Education Journal, 2019)
The aim of this study was to investigate the effect of directed reading thinking activity (DRTA) on students’ reading comprehension at second grade students of SMA Negeri 4 Bogor. The population of this study consisted of 60 secondary grade students at SMA Negeri 4 Bogor. The two groups’ including pre-post test true experimental design was used in this study. The instrument tools are students’ reading score such as pre-test and post-test such as summarizing and responding test; and reading assessment rubric. The result showed that t-calculated is 14.136 with the value of df is 58 while the result of t-table in the level significant t0.05 = 1.684 and t0.01 = 2.423. Since the t-calculated is higher than t-table (14.136 > 1.624 < 2.423), it can be concluded that the alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. It is concluded that Directed Reading Thinking Activity (DRTA) effects on student’s reading comprehension.